Operational Risk Management and Business Continuity Planning for Modern State Treasuries. (Technical Notes and Manuals; Technical Notes and Manuals, 2011)
This technical note and manual addresses the following main issues: 1. What is operational risk management and how this should be applied to treasury operations. 2. What is business continuity and disaster recovery planning and why it is important for treasury operations? 3. How to develop and implement a business continuity and disaster recovery plan using a six practical-step process and how to have it imbedded into the day-to-day operations of the treasury. 4. What is needed to activate and what are the key procedures when activating the disaster recovery plan.